2019
DOI: 10.19137/cienvet-201921206
|View full text |Cite
|
Sign up to set email alerts
|

Possible clinical leptospirosis in two cats (Felis silvestris catus) from the south of the Santa Fe province

Abstract: Sección: Artículos de investigación Posible leptospirosis clínica en dos gatos (Felis silvestris catus) del sur de la provincia de Santa Fe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
(36 reference statements)
0
0
0
Order By: Relevance
“…However, some studies reported the presence of anorexia, dyspnea, chronic diarrhea, interstitial nephritis, and hepatitis in cats infected with pathogenic Leptospira spp. (14)(15)(16)(17)(18). The International Society of Companion Animal Infectious Diseases (ISCAID) statement indicated that the main serovars detected in this species are L. interrogans serovars Icterohaemorrhagiae, Canicola, Pomona, Bratislava, and Autumnalis; L. kirschneri serovar Grippotyphosa; and L. borgpetersenii serovars Hardjo and Ballum (6).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies reported the presence of anorexia, dyspnea, chronic diarrhea, interstitial nephritis, and hepatitis in cats infected with pathogenic Leptospira spp. (14)(15)(16)(17)(18). The International Society of Companion Animal Infectious Diseases (ISCAID) statement indicated that the main serovars detected in this species are L. interrogans serovars Icterohaemorrhagiae, Canicola, Pomona, Bratislava, and Autumnalis; L. kirschneri serovar Grippotyphosa; and L. borgpetersenii serovars Hardjo and Ballum (6).…”
Section: Introductionmentioning
confidence: 99%